2013
DOI: 10.1111/jdv.12281
|View full text |Cite
|
Sign up to set email alerts
|

Atopy as a risk factor for thyroid autoimmunity in children affected with atopic dermatitis

Abstract: Our results therefore suggest that atopy, especially food allergy, and autoimmunity are two potential outcomes of dysregulated immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 19 publications
2
43
0
2
Order By: Relevance
“…In contrast, several clinical studies have reported the co-incidence of autoimmune and allergic diseases recently, and there is an increasing interest in the relationship between autoimmune and allergic diseases (29). Immune dysregulation secondary to an infectious agent or excessive exposure to a cross-reactive inciting antigen that promotes Th1 response leading to progressive inflammation and autoimmunity is the generally accepted model in the pathogenesis of autoimmune diseases (29). In mutually exclusive patient populations, Th1-type autoimmune disorders and Th2-type mediated allergic disorders would occur and this was predicted by the reciprocal counter-regulation of Th1 and Th2 cells (30).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, several clinical studies have reported the co-incidence of autoimmune and allergic diseases recently, and there is an increasing interest in the relationship between autoimmune and allergic diseases (29). Immune dysregulation secondary to an infectious agent or excessive exposure to a cross-reactive inciting antigen that promotes Th1 response leading to progressive inflammation and autoimmunity is the generally accepted model in the pathogenesis of autoimmune diseases (29). In mutually exclusive patient populations, Th1-type autoimmune disorders and Th2-type mediated allergic disorders would occur and this was predicted by the reciprocal counter-regulation of Th1 and Th2 cells (30).…”
Section: Discussionmentioning
confidence: 98%
“…However, there have not been enough studies in the literature showing the relationship of ITP with pollens, other allergens or with atopy. In contrast, several clinical studies have reported the co-incidence of autoimmune and allergic diseases recently, and there is an increasing interest in the relationship between autoimmune and allergic diseases (29). Immune dysregulation secondary to an infectious agent or excessive exposure to a cross-reactive inciting antigen that promotes Th1 response leading to progressive inflammation and autoimmunity is the generally accepted model in the pathogenesis of autoimmune diseases (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the normal-weight children without ADHD also compromised children with atopic diseases such as bronchial asthma and atopic dermatitis. Atopic diseases have been reported to be associated with elevated TSH levels in childhood [31, 32]. However, this alteration of TSH has mainly been attributed to autoimmune thyroiditis [31, 32], which formed an exclusion criterion in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Представляет интерес также факт обнаружения существенной ассоциации выявления ААТ к тирео идной пероксидазе у женщин с БА [28], что свиде тельствует о высоком риске наличия скрытого ауто иммунного тиреоидита (относительный риск -3,3; р < 0,01). Повышенный уровень антитиреоидных АТ был обнаружен и в сыворотке крови у детей с атопи ческим дерматитом и БА [29], следовательно, лица с аллергической патологией нуждаются в обязатель ном и раннем обследовании функции щитовидной железы [30].…”
unclassified